What Determines Sukuk Market Development? New Theoretical Insights - Aman, Ameen Ullah; Mohamed Naim, Asmadi; Isa, Mohamad Yazid (Faculty of Islamic Economics and Business, State Islamic University (UIN) Sunan Kalijaga, 2019)
In recent past, the Asian economies faced various financial crises, 1997 & 2008, because of underdeveloped or small capital markets. Most of the countries continued to heavily depend on the mere banking system for sovereign and corporate financing needs which made the region repeatedly vulnerable to the crises state. Therefore, the last decade has witnessed the remarkable growth in the alternative arrangement in the form sukuk and bond markets. The academic literature on the topic mainly focuses on bond market ignoring largely the determinants of sukuk market. Using content analysis approach, this conceptual study proposes the theoretical relationships of sukuk with some new possible determining factors along with some other factors which have not received enough attention in the literature. The study focuses on the dynamics of foreign capital inflows, macroeconomic and financial variables with respect to sukuk market development